STRATEGI BELAJAR BERBASIS ANALISIS PSIKOLOGI DAN PENERAPAN ANTAR GENERASI - Gilang Ramadhan Akbar; Jauhar Akbar Rosyid; Maulana Hakim Al Rasyid (STKIP Subang, 2023)
With the development of the times and the rapid flow of globalization, changes in the character of students change rapidly. Times change very quickly and develop so that generations change very quickly. There are several major differences between generations which are also caused by changes in social structure and technological advances, starting from the point of view, characteristics, and thoughts. Formal education from time to time also experienced development and change. Teachers must be able to be adaptive and also innovative which can make students have better quality. Therefore, it is important for teachers to apply appropriate learning strategies when teaching a student. If educators can properly apply learning strategies based on psychological analysis well, then this is aimed at none other than improving the quality and also the quality of humans so that life becomes better. This paper also explains that there are lines of difference in education between generations. Each generation has a different way of teaching strategies according to the era.